2018
DOI: 10.1186/s13046-018-0718-2
|View full text |Cite
|
Sign up to set email alerts
|

Osteoglycin (OGN) reverses epithelial to mesenchymal transition and invasiveness in colorectal cancer via EGFR/Akt pathway

Abstract: BackgroundMany types of cancers are devoid of the small leucine-rich proteoglycans: osteoglycin (OGN), but its role in tumorigenesis is poorly studied especially in colorectal cancers (CRC). Here we aim to evaluate the relationship between OGN expression patterns and the clinical course of CRC, and the role of OGN in cancer progression.MethodsThe tissue microarray staining was performed and the relevance between OGN expression and oncologic outcomes was performed using Cox regression analysis. The effect of OG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 30 publications
5
47
0
Order By: Relevance
“…Different signal pathways should be activated to regulate or influence OGN. Although many studies identified that the expression levels of OGN would alter in cancers, such as gastric cancer (Lee et al, 2003), colorectal cancer (Hu et al, 2018), and invasive ductal breast carcinoma (Roewer et al, 2011), functional data about how OGN participating in cancer pathology are not enough, and further studies are needed.…”
Section: Disscusionmentioning
confidence: 99%
“…Different signal pathways should be activated to regulate or influence OGN. Although many studies identified that the expression levels of OGN would alter in cancers, such as gastric cancer (Lee et al, 2003), colorectal cancer (Hu et al, 2018), and invasive ductal breast carcinoma (Roewer et al, 2011), functional data about how OGN participating in cancer pathology are not enough, and further studies are needed.…”
Section: Disscusionmentioning
confidence: 99%
“…Available expression data collectively suggest that OGN acts as a tumor suppressor, but functional analysis demonstrating the specific mechanisms through which OGN affects tumor progression is essentially lacking. In this issue of EBiomedicine, Hu and co-authors demonstrate a novel mechanism through which OGN limits tumor growth in colorectal cancer, namely through enhancing T-lymphocyte recruitment [ 2 ].…”
mentioning
confidence: 99%
“…High intratumoral expression of OGN is associated with prolonged patient survival in colorectal cancer, originally attributed to an inhibition of epithelial-mesenchymal transition (EMT) and reduced tumor invasiveness [ 2 ]. In the present study, Hu et al demonstrate a correlation between OGN expression and T-cell infiltration in human tumors by combining expression data from publicly available databases and in-house patient cohorts.…”
mentioning
confidence: 99%
“…Given the high number of cancer types exhibiting a coordinated expression decrease (or increase) of these core secretome genes, we reasoned that these genes would likely be responsible for important tumor-specific functions. Many of the genes exhibiting decreased expression are putative or established tumor suppressors (e.g., ANGPTL1, C2orf40, CHRDL1, OGN, C7, GREM2) ( Hu et al, 2018 ; Kuo et al, 2013 ; Li et al, 2015 ; Pei et al, 2017 ; Tsubamoto et al., 2016 ; Ying et al, 2016 ), are involved in the remodeling of the extracellular matrix (ECM) (e.g., DNASE1L3, CLEC3B, PI16, CCBE1) ( Barton et al, 2010 ; Hawes et al., 2015 ; Hazell et al, 2016 ; Obrist et al, 2004 ), and/or participate in cell-matrix adhesion functions (e.g., MFAP4, DPT, MAMDC2) ( Avilés-Vázquez et al, 2017 ; Pilecki et al, 2016 ; Yamatoji et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%